Estimating the effects of tsetse control on livestock productivity - a case study in southwest Ethiopia - Rowlands, G.J.; Mulatu, W.; Leak, S.G.A.; Nagda, S.M.; D'Ieteren, G.D.M. (Springer, 1999)
A tsetse control campaign was started in January 1991 using a synthetic pyrethroid cypermethrin `pour-on' applied monthly to cattle exposed to high levels of drug-resistant trypanosomes in the Ghibe valley of southwest Ethiopia. In December 1992, a cost-recovery scheme was introduced, and thereafter farmers paid for treatment. An average of 100 village Ethiopian Highland Zebu cattle were monitored monthly from March 1986 to February 1997. Individual animals in this herd were treated with diminazene aceturate (Berenil, Hoeschst, Germany) at 3.5 mg/kg when trypanosomes were detected and their packed cell volume was less than 26 percent. Superimposed on this systematic trypanocidal chemotherapy, contol of tsetse resulted in average reductions from 1992 to 1996 of 95 percent and 75 percent in the mean relative densities of tsetse and biting flies, respectively, and of 63 percent in the prevalence of trypanosomal infections in cattle. Despite these reductions, there was no significant increase in the body weight of the cows, calving rate or the mean body weight of calves at 12 months of age. There was, however, an average decrease of 57 percent in calf mortality (including still births) by 12 months of age, an increase of 49 percent in the ratio of live calves under 12 months of age to cows over 36 months of age, and an increase of 8 percent in the body weight of adult males.